Automated synthesis of technological fixture constructions - D P. Kunkevich; I. I. Polozkov; A. A. Baryshev (Системный анализ и прикладная информатика)
At the initial stage of engineering design it has to determine the set of units of design object and topological relations between them. The solution making at this stage is very efficiently because the set of operations may be carried out: adding components into the project, mating them to each other’s etc. The procedures of such kind are monotonous and time consuming. Article is dedicated to automation of topological design. However, the creation and adoption of design decisions is a difficult creative task. Currently, there are several approaches that can be applied to specific types of objects, such as injection molds, blacksmith dies, etc. Most of them are various kinds of technological equipment. There is another type of such equipment – fixtures for locating and clamping parts on the technological operations of assembly, welding, cutting, etc. Automated synthesis of fixtures is considered in this article. A method for determining the design situation is proposed. The method is based on location theory and involves the analysis of a solid model of the object being located. An example of carrier system is presented too. It is assumed that the content of the article will be useful for development of application based on CAD system. Moreover, the engineer – CAD-user himself can do this without involving a professional programmer.